How does telecommunications infrastructure affect eco-efficiency? Evidence from a quasi-natural experiment in China. (May 2022) - Tang, Chang; Xue, Yan; Wu, Haitao; Irfan, Muhammad; Hao, Yu
Abstract: Informatization and digitization have become breakthrough topics in China's economic development and environmental governance. In the same vein, knowledge, technology spillovers, and economic agglomeration effects of telecommunications infrastructure may enhance eco-efficiency. This study adopts the heterogeneous timing difference-in-difference (DID) model and event study method to evaluate the impact of telecommunications infrastructure on eco-efficiency using city-level data from 2008 to 2018 and the quasi-natural experiment of the Broadband China policy. The results indicate that telecommunications infrastructure exerts a significant positive impact on eco-efficiency, which is still validated after time trend assessment, PSM-DID estimation, instrumental variable test, and placebo test. In addition, regarding its impact mechanism, telecommunications infrastructure can promote eco-efficiency growth through green innovation, industrial structure upgrading, and resource allocation efficiency. Moreover, the heterogeneity analysis results suggest that the positive effects of telecommunications infrastructure on eco-efficiency are more noticeable in developed and higher eco-efficiency cities and cities with better transportation infrastructure conditions or higher marketization levels. The study findings incorporate telecommunications infrastructure and eco-efficiency into a unified research framework, providing a new perspective to improve eco-efficiency. Highlights: Telecommunications infrastructure exerts a significantly positive impact on eco-efficiency. The Broadband China pilot policy is regarded as a quasi-natural experiment. Eco-efficiency is measured based on nonradial and nonangular SBM and DDF models. The mechanism of the effect includes green innovation, emission reduction, and resource allocation. More competitive location conditions, better transportation infrastructure conditions and a higher level of marketization are conducive to the positive effects of telecommunications infrastructure.